Stiffness profiles of residual soil sites using continuous surface wave method - Aung, Aung Myo Win (2013)
In this study, continuous surface wave (CSW) tests were conducted to study the dispersion characteristics and stiffness profiles of two unsaturated residual soil sites in Singapore. Rayleigh wave dispersion curves were obtained by plotting measured Rayleigh wave phase velocities (Vĳ) against frequency. Dispersion characteristics of both sites were found to be normally dispersive. Stiffness profiles were then determined through inversion analyses. The stiffness profiles were found to be in good agreement with stiffness estimated from standard penetration test (SPT) and cone penetration test (CPT) data. The degree of weathering with depth at the two sites was also estimated from stiffness profiles. It was found that both sites have been heavily weathered to a substantial depth.